2018
DOI: 10.4236/aim.2018.87038
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Trends in Resistance to Fluoroquinolones and Extended Spectrum Beta-Lactams among <i>Salmonella</i> Typhi Isolates Obtained from Patients at Four Outpatient Clinics in Nairobi County, Kenya

Abstract: Typhoid fever caused by the bacterium Salmonella enterica serovar Typhi (S.Typhi) causes an estimated 25 million illnesses and approximately 200,000 deaths annually mostly in developing countries. Although the management of typhoid fever has been effectively through antibiotic treatment, S. Typhi is increasingly becoming resistant to the currently recommended drugs. This study utilized a quasi-experimental design focusing on archived samples to describe antimicrobial susceptibility patterns of S. Typhi and det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Mukuru Settlement is one of Nairobi’s largest and most crowded urban slums and is home to over 250,000 people [ 6 ]. As an informal settlement, there is a shortage of safe drinking water and inadequate infrastructure and sanitation, which predisposes people to typhoid fever [ 1 ]. Moreover, patients have easy access to over-the-counter medications, which fuels the growth and spread of antibiotic resistance [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Mukuru Settlement is one of Nairobi’s largest and most crowded urban slums and is home to over 250,000 people [ 6 ]. As an informal settlement, there is a shortage of safe drinking water and inadequate infrastructure and sanitation, which predisposes people to typhoid fever [ 1 ]. Moreover, patients have easy access to over-the-counter medications, which fuels the growth and spread of antibiotic resistance [ 15 ].…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, patients have easy access to over-the-counter medications, which fuels the growth and spread of antibiotic resistance [ 15 ]. For instance, Kavai et al (2018) reported an MDR prevalence of 55.5% in S. Typhi isolates from outpatient clinical samples from Mukuru villages in Nairobi [ 1 ]. To effectively develop typhoid control and prevention methods, it is important to understand the epidemiological dynamics of Salmonella Typhi in this setting.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Salmonella strains were obtained from the Centre for Microbiology Research (CMR) at the Kenya Medical Research Institute (KEMRI) [17,18] and Kenyatta national hospital [14] in Nairobi, Kenya. The isolates were confirmed using slide agglutination techniques, conventional…”
Section: Bacterial Strainsmentioning
confidence: 99%